Konsep Pengembangan Potensi Pesisir Pantai Desa Semare Menuju Desa Ekowisata CafÃ© Laut Semare (CLS) - Maftuch, Maftuch; Sugiarto, Sugiarto; Hoetoro, Arif; Adam, Moh. Awaludin (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Semare village has the potential of nature to developed to ecotourism village, located north of Pasuruanregency of East Java. Community service is done by formulating the concept of Semare Village development, KecamatanKraton, Pasuruan to an independent village with basic development of coastal village through Semare Sea Cafe concept(CLS) and strategy to be pursued in succeeding concept that has been formed. Community service is carried out for 6 (six)months, ie February 2018 to July 2018 in Coastal Village Semare, Pasuruan Regency. The methods used in this devotionare field observation, Foccus Group Discussion (FGD), comparative study and graphic design to get the CLS design inline with the expectations of Semare Village residents. Meanwhile, to find out how much participation in villagedevelopment conducted by the community is analyzed menggungan method of Rapid Rural Appraisal (RRA). Villagepartner development activities that have been implemented during the first year with the aim of introducing andsocializing the mindset waterfront village in Semare Village community have a positive impact. This is reflected in thebehavior and attitude of the people who have consciously organized the coastal environment to a village that is at leastworth visiting. The villagers are very enthusiastic to succeed the event. So in the second year of service activity is moreemphasized on the study activity of Village Ecotourism based on community participation